The main City Branding Dimensions in Health Tourism Development:A scoping review - Asadzadeh, Mahboobeh; Vatankhah, Soudabeh; Aryankhesal, Aidin (The journal of contemporary issues in business and government, 2021)
Health tourism industry is rapidly growing across different countries and make a lot of financial economic benefits.A deep understanding of a destination for health tourism can provide strong perspectives to promote competitive advantage with low cost. The present study aimed to determine city branding dimensions for health tourism development. This study was performed in four databases search: PubMed, Embase, Scopus, and WOSwithout any time limitations to identify relevant literature about city branding and healthtourism. In total, 15595 records were identified from all databases. Finally, a total of 24 publications were included in the qualitative analysis. The finding indicated infrastructure, landscape, and structure as three main city branding dimensions in health tourism development.The results also showed that there is a consensus thatif proper marketing and brand planning will be done for a city based on these three dimensions, it can make a positive image for health tourism destinations.